Analysis on Changes in Water Level-Flow of the Pearl River Basin in Recent Years and Its Causes - TANG Jiaqi; DUAN Kai; HAO Lu (Renmin Zhujiang)
Aiming at the impact of climate change and rapid urbanization on the hydrological situation in the Pearl River Basin in recent years,this paper analyzes the evolution trend and variation characteristics of the water level,flow and water level-flow of 16 major hydrological stations in the Pearl River Basin from 1997 to 2013,and discusses the causes of the evolution of water level and flow in each sub-basin based on the meteorological,hydraulic engineering,and water and sediment data in the historical period.The results show that:①The average annual flow of most stations in the Pearl River Basin didn't change significantly,but the Jiangbianjie,Chongwei and Liuzhou stations in the Xijiang River Basin showed a significant reduction trend;②The flow of most stations in the flood season decreased,while that in the dry season increased.The different precipitation during the dry/flood season was the important factors leading to the change of flow in the Pearl River Basin;③The water level of most stations in the Xijiang River Basin showed a significant upward trend,which was caused by the aggravating water and soil loss.While under the influence of reservoir operation and sand mining activities,the Beijiang River Basin and the lower reaches of the Dongjiang River Basin showed a trend of riverbed down-cutting and water level lowering.